In-silico screening, pharmacokinetic evaluation, DFT study, and molecular dynamic simulation as approaches for the identification of acetamide and acetic acid derivatives as potential antisickling agents targeting Hba protein - Stephen Ejeh; Abduljelil Ajala; Samuel Ndaghiya Adawara; Olasupo Sabitu Babatunde; Zakari Ya’u Ibrahim; Usman Abdulfatai (Discover Chemistry)
Abstract One of the most prevalent genetic conditions is sickle cell disease (SCD), a multiorgan condition that impacts about 15 million people around the globe. The current standard of care for SCD mainly consists of hydroxyurea therapy or supportive care, which includes hydration, blood transfusions, and pain control. The FDA recently approved strategies that lower the frequency of vaso-occlusive crisis (VOC) events, including the monoclonal P-selectin and the small molecule L-glutamine. The search for drugs that bind to Hb and alter the oxygenation state allostery has been a key therapeutic area for SCD. In this study, computational methods such as in silico screening, pharmacokinetic evaluation, DFT study, and molecular dynamic simulation were used to identify lead compounds as natural antisickling agents. The idea was to search PubChem databases for novel bioactive plant compounds with the potential to prevent SCD effectively. The PubChem databases were screened based on the binding energy (BE), pharmacokinetics properties, DFT study, and MD simulation, and 3 molecules with PUBCHEM_CID 20684853, 44461326, and 137225065 out of the 157 compounds examined were identified as active candidate hits with BE of − 177.35 kcal, − 175.11 kcal, and − 182.13 kcal, respectively, as compared to − 173.08 kcal of P-Selectin, which indicated that it is more stable and requires more energy to dissociate. When compared to P-Selectin as the standard drug, these molecules showed the best pharmacokinetic properties and potency.